2023
DOI: 10.3389/fenvs.2022.1076859
|View full text |Cite
|
Sign up to set email alerts
|

The impact of renewable energy transition, green growth, green trade and green innovation on environmental quality: Evidence from top 10 green future countries

Abstract: Graphical AbstractGraphical illustration of D-H panel test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 108 publications
3
15
0
Order By: Relevance
“…Similarly, these results are also consistent with Can et al (2021), who demonstrated that green trade could promote the adoption of environment friendly industrial techniques and benefits countries in achieving their climate targets. Likewise, , and Wei et al (2023) also found similar results for positive long-run association between green trade and green economic growth for China and proposed long-term global integration of the nations to strengthen the production of green goods. International trade has made it possible for EMEs to produce and export green goods around the globe and import a wide range of green goods from other countries.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Similarly, these results are also consistent with Can et al (2021), who demonstrated that green trade could promote the adoption of environment friendly industrial techniques and benefits countries in achieving their climate targets. Likewise, , and Wei et al (2023) also found similar results for positive long-run association between green trade and green economic growth for China and proposed long-term global integration of the nations to strengthen the production of green goods. International trade has made it possible for EMEs to produce and export green goods around the globe and import a wide range of green goods from other countries.…”
Section: Resultssupporting
confidence: 57%
“…The study discovered that green trade substantially cuts greenhouse gas emissions. For the top 10 green future economies Wei et al (2023) considered the impact of green trade on environmental quality and findings showed that green trade boost quality of the environment. Research related to the impact of international trade on CEs yielded contradictory findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The variable used to represent the GG is selected when the studies in the literature are evaluated based on the data availability criterion for the country group at the relevant time, in accordance with Wei et al ( 2023 ) and Danish and Ulucak ( 2020 ).…”
Section: Dataset and Methodologymentioning
confidence: 99%
“…Similarly, Wei et al (2023) argued that the environmental quality of most green economies is significantly improved through ET improvement. Chen et al (2023b) found that ETs significantly help improve the environmental quality of G7 countries.…”
Section: Empirical Literature and Hypothesis Development 221 Environm...mentioning
confidence: 99%